2004
DOI: 10.1007/s00204-004-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of non-invasively acquired human genomic DNA as a substrate for real-time PCR-assisted analysis of genetic polymorphisms

Abstract: Molecular epidemiological studies require high numbers of participants. The combination of an non-invasive access to human DNA with a rapid genotyping analysis, e.g. by use of LightCycler assisted real-time polymerase chain reaction (PCR), can be helpful in conducting such trials. The aim of our study was to define, for the first time, the use of LightCycler technology in analysis of non-invasively derived DNA. DNA extracted from blood, mouthwash and buccal cytobrush samples from 100 volunteers was analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…] exceeded our minimum criterion, 18% of cytobrush samples and 24% of swab samples fell below this criterion. Our yield results for these two buccal scraping methods agree with those reported in previous studies, which suggests that at least two (Cozier et al, 2004;Freeman et al, 1997;King et al, 2002;Neuhaus et al, 2004;Saftlas et al, 2004) and as many as seven (e.g., Tanigawara et al, 2001) swabs or brushes per individual would be required to meet this criterion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…] exceeded our minimum criterion, 18% of cytobrush samples and 24% of swab samples fell below this criterion. Our yield results for these two buccal scraping methods agree with those reported in previous studies, which suggests that at least two (Cozier et al, 2004;Freeman et al, 1997;King et al, 2002;Neuhaus et al, 2004;Saftlas et al, 2004) and as many as seven (e.g., Tanigawara et al, 2001) swabs or brushes per individual would be required to meet this criterion.…”
Section: Discussionsupporting
confidence: 92%
“…The yield we observed for whole saliva is far greater than those reported by most previous studies of noninvasive DNA methods using cytobrush (Garcia-Closas et al, 2001;Saftlas et al, 2004), buccal swabs (Freeman et al, 1997;King et al, 2002;Meulenbelt et al, 1995), and oral rinse (Andrisin et al, 2002;Bauer et al, 2004;Cao et al, 2003;Cozier et al, 2004;Garcia-Closas et al, 2001;King et al, 2002;Le Marchand et al, 2001;Neuhaus et al, 2004;Tobal et al, 1989). Previous studies of DNA yield from whole saliva collected and processed by other methods (Harty et al, 2000;Ng et al, 2004;Terasaki et al, 1998;van Schie and Wilson 1997;Walsh et al, 1992) reported much lower yields than we observed using the Oragene TM kit (range, 8-30 mg), despite similar amounts of collected saliva (1-2 ml).…”
Section: Discussionmentioning
confidence: 97%
“…GSTP1 Ile 105 Val polymorphism (rs1695) was analyzed using fluorescence-based melting curve analysis as described previously [21]. Homozygous deletions of GSTM1 and GSTT1 were assessed using a multiplex PCR followed by gel electrophoresis as described previously [22].…”
Section: Methodsmentioning
confidence: 99%
“…These limitations include potentially limited quality and quantity of DNA obtained from buccal specimens4, 9, 13, 15, especially in children13, 16. Mouthwash rinsing is one of the most frequently used 10 alternative methods of collection for buccal cells DNA collection, and may produce DNA of higher quantity and purity than cytobrushes10, 17.…”
Section: Commentmentioning
confidence: 99%